Implementasi Kepemimpinan Spritual dalam Pengelolaan Pendidikan Islam di Lembaga Raudhatul Mutaallimin - Suci Urmilawati; Mohammad Muchlis Solichin; Ali Nurhadi (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to analyze the implementation of spiritual leadership in the management of Islamic education at Raudhatul Mutaallimin Institution. Spiritual leadership is an approach that emphasizes values such as faith, sincerity, trustworthiness, and exemplary behavior in carrying out responsibilities. This research uses a qualitative approach with a case study design. Data collection techniques include observation, in-depth interviews, and documentation, with research subjects consisting of the institution’s leader, teachers, and educational staff. Data analysis is conducted through data reduction, data display, and conclusion drawing, while data validity is ensured through triangulation. The results of the study show that spiritual leadership at Raudhatul Mutaallimin Institution is implemented in various aspects of management, such as decision-making based on deliberation and justice, guidance of teachers and staff through role modeling and togetherness, and the habituation of Islamic values in students’ daily activities. In addition, spiritual leadership plays a role in shaping a religious, disciplined, and harmonious institutional culture. The implementation of spiritual leadership has a positive impact on the institutional environment, teacher performance, and students’ character development. However, there are still several challenges, such as differences in understanding, limited human resources, and the demands of modern management. In conclusion, spiritual leadership can be an effective approach in improving the quality of Islamic education management, particularly in creating an educational environment that excels not only academically but also in moral and spiritual values.